Study of Type of Bacteria That Found in Ear, Mouth, Nose of Second Stage Nursing Department Student - Hala Abbas Jasim (Institute of Medico-legal Publications Pvt Ltd, 2020)
The samples collected from 70 nursing student second stage ,the sample was mouth ,ear ,nose .The samplecultured on nutrient agar ,MaCconkey agar ,Mannitol agar ,and brain heart agar. Observed different type ofbacteria on MaCconkey agar (lactose fermenting ,lactose non fermenting ,lactose slow fermenting ,Mucoidshape ,and different type of bacteria on Mannitol Agar and nutrient agar .after that the isolate tested withGram stain , Catalase test and then Analytic profile index perform. The results showed the bacteria is (5 )(0,5%)isolates of Staphylococcus aureus and (2)(0,2%) isolates of pseudomonas aeruginosa from 70 earsamples , (5 )(0,64%)isolates Staphylococcus aureus and ( 4 )(0,51%)isolates of Staphylococcus epidermedisfrom 70 mouth samples and 5(0,5%) isolates from pseudomonas aeruginosa ,(2)(0,2%) isolates of Serratiamarcescens from70 nose samples.And then the antibiotic sensitivity tested against :Ciprofloxacin ,Gentamycin,Vancomycin,Pencilin,Azithromycin,Cefex,Amikacin,levofloxacin3 and theresult as in table below :(Antibiotic sensitivity test result)AntibioticsBacteriaVA p ATM CN AK LEV CIPStaphylococcus aureus + - + + + + +Staphylococcus epedermidis - - + - + + +Pseudomonas aeroginosa + + + + + + +Serratia marcescens + - - - - + ++ mean sensitive , - mean resistant